2011
DOI: 10.1111/j.1365-246x.2011.05064.x
|View full text |Cite
|
Sign up to set email alerts
|

A theory for microtremor H/V spectral ratio: application for a layered medium

Abstract: International audienceMicrotremors are produced by multiple random sources close to the surface of the Earth. They may include the effects of multiple scattering, which suggests that their intensities could be well described by diffusion-like equations. Within this theoretical framework, the average autocorrelation of the motions at a given receiver, in the frequency domain, measures average energy density and is proportional to the imaginary part of the Green's function (GF) when both source and receiver are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
138
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 300 publications
(157 citation statements)
references
References 28 publications
0
138
0
3
Order By: Relevance
“…It has been established that if the H/V is defined as the square root of the ratio between the horizontal and the vertical energies of a Diffuse Field, it is then possible to express this ratio in terms of the imaginary components of the Green function (Sánchez-Sesma et al 2011a). In what follows, we summarize the arguments.…”
Section: Theoretical H/vmentioning
confidence: 96%
See 3 more Smart Citations
“…It has been established that if the H/V is defined as the square root of the ratio between the horizontal and the vertical energies of a Diffuse Field, it is then possible to express this ratio in terms of the imaginary components of the Green function (Sánchez-Sesma et al 2011a). In what follows, we summarize the arguments.…”
Section: Theoretical H/vmentioning
confidence: 96%
“…The second interpretation is due to Nakamura (1989;2000), who suggests that the ratio H/V is related to the transfer function for vertical incidence of SH waves; the success of the H/V measurements was spectacular but it came along with controversy about the interpretation of the resulting spectral ratios. On the other hand, Sánchez-Sesma et al (2010;2011a) have proposed recently that microtremors form a Diffuse Field containing all types of body (P and S) and surface waves (Love and Rayleigh). In a recent review, Lunedei and Malischewsky (2015) made a detailed description of the various theoretical models for the H/V spectral ratio developed in the last three decades.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it has been shown that a perfectly diffuse and equipartitioned wavefield is a necessary and sufficient condition to retrieve the exact Green's function (Sánchez-Sesma et al 2008) and although this hypothesis has been used to interpret some experimental features of the seismic noise wavefield there had already been some conjectures that the noise wavefield might not be totally equipartitioned and diffuse but anyhow dominated by this feature (e.g. Kawase et al 2011;Sánchez-Sesma et al 2011;Hillers et al 2012). As shown by Matsushima et al (2014), it is easy to theoretically construct a diffuse field for an inhomogeneous medium but, on the contrary, equipartition would not be realized for the case of a medium with distinctive geometrical features, even under the strong scattering situation or random wave incidences.…”
Section: Discussionmentioning
confidence: 99%